KINERJA BAZNAS KOTA MALANG MENURUT PERATURAN BAZNAS NOMOR 2 TAHUN 2016 TENTANG PEMBENTUKAN DAN TATA KERJA UNIT PENGUMPULAN ZAKAT - Asri Ainul Habibah; Mohammad Toriquddin; Luthfatul Qibtiyah (Al-Amien Prenduan for Islamic Institute, 2020)
This paper aims to describe the optimize the function of zakat collection unit (UPZ) in maximizing the performance of BAZNAS City of Malang according to BAZNAS Rule Number 2 of 2016. This research includes empirical legal research using a sociological juridical approach. Data collecting done by structured interviews and documentation and than analyzed by data reduction, data presentatiton and conclusions/verification. The results of this research that the Zakat Collecting Unit (UPZ) which is under the auspices of the National Amil Zakat Agency (BAZNAS) of Malang City carries out its duties and functions in broad outline in accordance with BAZNAS Rule Number 2 of 2016 concerning Formation and Work Procedures Zakat Collection Unit. Each UPZ has its own methods and methods in collecting or distributing zakat, infaq and alms (ZIS) funds. The National Amil Zakat Agency (BAZNAS) of Malang City recognizes the performance of the Zakat Collecting Unit (UPZ) to help Malang City BAZNAS in maximizing BAZNAS performance, especially in the distribution of zakat, infaq and alms (ZIS) funds to those who are entitled to receive them.